Faktor-Faktor yang memengaruhi Nilai Perusahaan Non-Keuangan di Bursa Efek Indonesia - Stephanus Julio Winata; Dewi Agustina (Media Bisnis, 2021)
The purpose of this research is to analyze empirically the influence of profitability, liquidity, dividend policy, debt policy, institusional ownership, company size,company age,company profit, managerial ownership, and company growth to firm value.Sample of this research are the listed non financial companies in Indonesian Stock Exchange from 2016 to 2018. The samples are collected using purposive sampling method and there are 85 companies or 255 data meet those criteria for samples.This research uses multiple regression method for data analysis.The result of this research shows that profitability,debt policy,institusional ownership, company size,company profit, and company growth do have influence firm value, but liquidity, dividen policy, company age, and managerial ownership do not have influence firm value. Keywords: firm value, profitability, liquidity, dividen policy, debt policy, institusional ownership, company size, company age, company profit, managerial ownership, company growth.